LIFE SKILL DEVELOPMENT THROUGH VOLLEYBALL SPORTS IN THE POSITIVE YOUTH DEVELOPMENT FRAMEWORK - Kusdinar, Yopi; Ma’mun, Amung; Rusdiana, Agus; Abdullah, Ade Gaffar (Universitas Pendidikan Indonesia, 2022)
A systematic review was conducted to investigate the literature on the effectiveness of comprehensive life skills programs. Life skills development has been linked to participation in sports in general, as well as volleyball and other physical activities that will be tried in Indonesia. This is aimed at encouraging the positive development of young people so that they have better opportunities for quality living in the future. This can happen when the coaches understand correctly how life skills are integrated structurally and intentionally in the process of volleyball training for the positive development of young people. This article will discuss matters relating to the types of environments that trainers need to create so that players can develop life skills, form a formal training process for trainers, and finally practice as well as experimentation on how life skills are integrated into volleyball training. The results of this experiment will be a further study to find out the special features of life skills integration that are integrated in a structured and intentional manner compared to unintentional structured and with no involvement at all in the context of positive development of young people.